Análise neurofuncional e antropométricade recém-nascidos de mães cronicamente infectadas pelo Toxoplasma gondii - Riesco, Thaís Bandeira (2016)
Introduction: Toxoplasma gondii is the etiological agent of a parasitic parasitic disease of universal distribution, with infected individuals in all countries. The main forms of contagion are through the ingestion of different parasite evolutionary forms present in raw meats or undercooked, unfiltered water, unpasteurized milk, contaminated soil handling and contact with infected cats. Clinical disease is less frequent and the most severe forms can be found when congenital transmission occurs and in immunocompromised patients. When the fetus touches this infectious agent and survive, it can present several problems such as: restriction in the intrauterine growth, premature birth, microcephaly, hydrocephalus, brain calcifications, pneumonitis, hepatosplenomegaly, skin rash, intellectual disability, among others. The consequences to the fetus are higher in the first trimester of pregnancy and the transmissibility in the third trimester is the highest. The degree of commitment of the newborn will depend on the gestational period in the moment of the first transmission of the illness and the pregnant woman. Objective: The objectives of this study were to evaluate perceptible alterations in the neuropsychomotor examination and in anthropometric measures of newborns (RNs) of chronically infected mothers by Toxoplasma gondii. Methods: The study was performed in a population of 79 children of puerperal mothers, 41 of them were children of mother with infection of toxoplasmosis and 38 were children of not infected mother by the protozoan. It was made out a sociodemographic interview with these mothers through a questionnaire and an examination of primitive reflexes in their respective children. The study was conducted in one maternity of standard for risk pregnancy, in the city of Goiânia, Goiás, in the period from June 2015 to June 2016. The analysis were performed with the aid of the statistical package SPSS®, version 23. The serologic testing for confirmation of toxoplasmosis infection and absence of anti-T gondii in the mothers serum was made by Immunoassay of Microparticles by Chemiluminescense (CMIA). Results: Neuropsychomotor examination the absence of reflection escape the suffocation was found in two children of chronically infected mothers. In the comparison of the thoracic perimeter and the cephalic perimeter 31/79 children were classified as inadequate and two children of mothers chronically infected were too small for their gestational age. Conclusion: In relation to the neuropsychomotor examination and anthropometric measurements, in the group of newborn of puerperal mothers chronically infected by Toxoplasma gondii could not detect any perceptible alterations when in comparison to the control group of susceptible mothers.